2021
DOI: 10.3390/cancers13164159
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Multidisciplinary Team Meetings on Clinical Practice for Colorectal, Lung, Prostate and Breast Cancer: A Systematic Review

Abstract: Objective: The aim of our systematic review is to identify the effects of multidisciplinary team meetings (MDTM) for lung, breast, colorectal and prostate cancer. Methods: Our systematic review, performed following PRISMA guidelines, included studies examining the impact of MDTMs on treatment decisions, patient and process outcomes. Electronic databases PUBMED, EMBASE, Cochrane Library and Web of Science were searched for articles published between 2000 and 2020. Risk of bias and level of evidence were assesse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 60 publications
1
33
0
Order By: Relevance
“…Systematic literature reviews and metanalyses (SLRs) conducted according to the PRISMA guidelines (including an evidence-based minimum set of items for reporting) ( , accessed on 8 May 2021) are increasingly important in health care, keeping medical doctors up to date, and also representing the background for developing clinical guidelines/trials, as well as the justification for financial supports of research projects. Usually conducted by multidisciplinary teams, SLRs performed according to these guidelines could be applicable in various topics/contexts, improving the research quality not only of pure meta-analyses but also of SLRs applied to case report/series [ 215 , 216 , 217 , 218 , 219 , 220 , 221 , 222 , 223 , 224 , 225 , 226 , 227 , 228 , 229 , 230 , 231 , 232 , 233 , 234 , 235 , 236 , 237 , 238 , 239 , 240 , 241 , 242 , 243 , 244 , 245 , 246 , 247 , 248 , 249 , 250 , 251 , 252 , 253 , 254 , 255 , 256 , …”
Section: Discussionmentioning
confidence: 99%
“…Systematic literature reviews and metanalyses (SLRs) conducted according to the PRISMA guidelines (including an evidence-based minimum set of items for reporting) ( , accessed on 8 May 2021) are increasingly important in health care, keeping medical doctors up to date, and also representing the background for developing clinical guidelines/trials, as well as the justification for financial supports of research projects. Usually conducted by multidisciplinary teams, SLRs performed according to these guidelines could be applicable in various topics/contexts, improving the research quality not only of pure meta-analyses but also of SLRs applied to case report/series [ 215 , 216 , 217 , 218 , 219 , 220 , 221 , 222 , 223 , 224 , 225 , 226 , 227 , 228 , 229 , 230 , 231 , 232 , 233 , 234 , 235 , 236 , 237 , 238 , 239 , 240 , 241 , 242 , 243 , 244 , 245 , 246 , 247 , 248 , 249 , 250 , 251 , 252 , 253 , 254 , 255 , 256 , …”
Section: Discussionmentioning
confidence: 99%
“…The clinical management of patients by MDT has now entered clinical practice and is recommended by several oncologic guidelines, 26,27 although the implementation is heterogenous worldwide, 28 especially in developing countries. 29 It is well established that the accuracy of diagnosis is improved, with the indication to perform examinations to guarantee a more complete staging [14][15][16][17]30 and cancer care can be improved using newly developed electronic health record and cloudbased software. 11,12,31 Consequently, treatment is also modified and integrated among all the specialists taking part in the discussion, thus increasing the adherence to the guidelines.…”
Section: Discussionmentioning
confidence: 99%
“…10 While it has been shown that MDTs lead to more accurate staging, 11 higher adherence to clinical guidelines, 12 and shorter time to treatment after diagnosis, 13 several prior studies have failed to show improved outcome among patients discussed in MDT meetings [14][15][16] while other have reported better outcomes. [17][18][19] The MDT conference is a costly process, and it is important that future studies justify the costs through evidence of better outcomes.…”
Section: Discussionmentioning
confidence: 99%